Federated quantum-inspired anomaly detection using collaborative neural clients - Godavarthi, Deepthi; Rekapalli, Venkata Charan Sathvik; Mohanty, Sribidhya; Jaswanth, J. V. S. D. Vigneswara; Polisetty, Dinesh; Dash, Bibhuti Bhusan; Moreira, Fernando (Frontiers in Artificial Intelligence, 2025)
IntroductionThe fusion of deep-learning-based and federated methods has brought great progress in anomaly detection. Yet the systems of today still suffer from certain glaring issues. First, aggregation of data on a central entity poses dangerous privacy hazards. Second, such models could not scale and adapt to heterogeneous and distributed environments. Lastly, fine consideration has hardly been given to quantum-inspired computational paradigms that may promise to improve both speed and security of such systems. To fill in these gaps, this research proposes a completely novel quantum-inspired federated learning approach to anomaly detection that keeps data private and allows for further implementations of quantum computing applications.MethodsThe proposed system works on a client-server architecture comprising multiple clients, which either run training of local feedforward neural networks on different private subsets of their data or choose to not participate during an iteration. Clients never pass raw data to the server but instead alternate by sending the server the parameters of the trained model. The server aggregates these local updates by the FedAvg algorithm and produces the global model. The present implementation focuses mainly on utilizing classical deep learning; however, the architecture is made flexible enough to intertwine smoothly with quantum machine-learning paradigms in the future, thus enabling quantum technological enhancement down the road without requiring the entire system to be rebuilt.ResultsThe framework could produce up to 79% of anomalous detection accuracy. The system had effective learning across distributed clients whilst ensuring that no piece of private data was being shared or spilled (exposed) between clients. These results ensured that the framework maintained its performance while keeping its privacy intact, a very crucial consideration on which to ever really deploy such in sensitive areas.DiscussionThe approach allows privacy-preserving anomaly detection across multiple domains and serves as a framework for enlarging and scaling the system. Being quantum-inspired compatible allows for future-proofing and further expediting and enhancing security. The system, having the capability to securely work in a distributed manner, can, thus, be utilized in critical information domains like cybersecurity, finance, and healthcare, where privacy of data is deemed extremely important. This work, thereby, offers a useful federated learning approach towards anomaly detection while going a step further towards the incorporation of quantum computing into secure, distributed AI systems.